Physical Properties and Panelists’ Preference for Purple Sweet Potato Flour Flakes with Okara Flour Substitution - Sulthan Haz Syafiq Mubarok; Dwi Agustiyah Rosida; Tiurma Wiliana Susanti Panjaitan (Agricultural Science, 2025)
Purple sweet potato flour is a promising flake component due to its elevated carbohydrate and antioxidant levels. Nonetheless, its very low protein content requires the incorporation of supplementary ingredients, such as okara flour, which is abundant in protein and fiber, to enhance the nutritional profile of the final product. This study investigates the impact of replacing purple sweet potato flour with okara flour on flakes' physical properties (texture and rehydration capacity) and sensory acceptance (organoleptic qualities). A one-factor Completely Randomized Design (CRD) was employed with five replacement levels: P0 (100%:0%), P1 (90%:10%), P2 (80%:20%), P3 (70%:30%), and P4 (60%:40%). The results showed that the substitution markedly influenced texture (p = 0.016) and rehydration capacity (p = 0.000), with increased okara levels resulting in firmer flakes and enhanced rehydration. Substitution markedly affected panelists' preferences for taste (p = 0.000), texture (p = 0.000), and color (p = 0.025), but not scent (p = 0.725). Elevating okara levels often diminished preference for flavor and texture, although color was favored at elevated okara concentrations. The optimal formulation was achieved with a 20% replacement of okara.